2018
DOI: 10.1158/1535-7163.mct-18-0038
|View full text |Cite
|
Sign up to set email alerts
|

Cotargeting the Cell-Intrinsic and Microenvironment Pathways of Prostate Cancer by PI3Kα/β/δ Inhibitor BAY1082439

Abstract: Targeting the PI3K pathway is a promising strategy for treating prostate cancers with PTEN-loss. However, current anti-PI3K therapies fail to show long lasting effects. We find that not only the PI3Kα- and PI3kβ-isoforms, but also PI3Kδ, are associated with the epithelial-mesenchymal transition (EMT), a critical process distinguishing indolent from aggressive prostate cancer. This suggests that cotargeting PI3Kα/β/δ could preempt the rebound activation of the parallel pathways induced by α- or β-isoform-select… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 28 publications
3
14
0
Order By: Relevance
“…E3330 was the first APE1 redox inhibitor to be identified, [25] and it has been the most widely studied. As described in the literature, at commonly used inhibitory concentrations of the APE1 redox function (e.g., up to 50 μm), [14,17,32,[46][47][48] E3330 did not interfere with APE1 endonuclease activity. [31,32,49] We also performed a fluorescence-based endonuclease activity assay [50] and confirmed that E3330 at 30 μm did not inhibit APE1 DNA repair function (data not shown).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…E3330 was the first APE1 redox inhibitor to be identified, [25] and it has been the most widely studied. As described in the literature, at commonly used inhibitory concentrations of the APE1 redox function (e.g., up to 50 μm), [14,17,32,[46][47][48] E3330 did not interfere with APE1 endonuclease activity. [31,32,49] We also performed a fluorescence-based endonuclease activity assay [50] and confirmed that E3330 at 30 μm did not inhibit APE1 DNA repair function (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…[6,7] APE1 is usually referred as a dual-function protein because it has also an independent role as a reduction/oxidation signalling protein, modulating the activation of several transcription factors through the reduction of cysteine residues in their DNA-binding domains. Consequently, APE1 regulates the ability of transcription factors, such as nuclear factor-кB (NF-кB), [8] activator protein 1 (AP-1), [9] early growth response protein-1 (Egr-1), [10,11] hypoxia-inducible factor 1α (HIF-1α), [12][13][14] p53, [15,16] signal transducer and activator of transcription 3 (STAT3) [17] among others, to bind to their specific DNA sequence and promote the expression of genes implicated in cancer cell survival, proliferation, migration/invasion, angiogenesis and metastases formation. [6,7] More recently, the redox function of APE1 has been shown to be involved in the regulation of WNT/β-catenin signalling pathway in pancreatic cancer cells.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations